2020
DOI: 10.3389/fnins.2020.00593
|View full text |Cite
|
Sign up to set email alerts
|

EEG Channel-Selection Method for Epileptic-Seizure Classification Based on Multi-Objective Optimization

Abstract: We present a multi-objective optimization method for electroencephalographic (EEG) channel selection based on the non-dominated sorting genetic algorithm (NSGA) for epileptic-seizure classification. We tested the method on EEG data of 24 patients from the CHB-MIT public dataset. The procedure starts by decomposing the EEG data from each channel into different frequency bands using the empirical mode decomposition (EMD) or the discrete wavelet transform (DWT), and then for each sub-band four features are extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…In this problem, a bi-objective function with two criteria (error rate and the number of channels) was used to obtain a robust trade-off between the number of channels and the classification accuracy. In recent work, the Multi-Objective Non-Sorting Genetic Algorithm (MO-NSGA) algorithm, is used for channel selection [48]. This method employed a hybrid signal feature set using Empirical Mode Decomposition (EMD) and Discrete Wavelet Transform (DWT) with MO-NSGA algorithm and achieved 100% classification accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…In this problem, a bi-objective function with two criteria (error rate and the number of channels) was used to obtain a robust trade-off between the number of channels and the classification accuracy. In recent work, the Multi-Objective Non-Sorting Genetic Algorithm (MO-NSGA) algorithm, is used for channel selection [48]. This method employed a hybrid signal feature set using Empirical Mode Decomposition (EMD) and Discrete Wavelet Transform (DWT) with MO-NSGA algorithm and achieved 100% classification accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…This algorithm has been applied to EEG channel selection for classification of motor imagery Kee et al (2015). Moreover, the algorithm has proven to be effective in identifying low-density EEG subsets that maximize classification accuracy while reducing the number of EEG channels required for epileptic seizure classification (Moctezuma and Molinas (2020a)) and subject identification (Moctezuma and Molinas (2020b)).…”
Section: Electrode Optimization For Source Reconstructionmentioning
confidence: 99%
“…Nevertheless, none of those studies showed the machine learning validating performance comparisons between results with selected channels and results with all channels. Moctezuma and Molinas [ 15 ] decomposed the EEG data from each channel into different frequency bands using the empirical mode decomposition (EMD) or the discrete wavelet transform (DWT) for the channel selection. The results showed accuracies of up to 100% with only one EEG channel in the epileptic seizure classification, while all the test results of channels were less than 100%; however, this research only classified the seizure and non-seizure signals, not the pre-ictal signals.…”
Section: Introductionmentioning
confidence: 99%